KAJIAN PENERAPAN PENDAMPINGAN PENELITIAN TINDAKAN KELAS KOLABORATIF ANTARA PERGURUAN TINGGI DAN SEKOLAH - Zulfiani Zulfiani; Yanti Herlanti; Ahmad Sofyan (LPMPP Universitas Negeri Yogyakarta, 2016)
This study aims to find a collaborative assistance model of Classroom Action Research between universitiy and school (CAR Collaborative). Research was done at Biology Education Departement UIN Syarif Hidayatullah partner schools that located in South Jakarta, Bogor, and South Tangerang. Research have done for 10 months in February to November 2015. The Mixed Method was used in this reserach. Some instrument for data collecting are questionnaire, depth interview guide, and note field. The results showed three CAR assistance models of collaboration i.e Model I (dominant teachers-oriented), Model II (moderate-teacher oriented), and Model III (resesive teacher-oriented). Model I teacher and lecturers do PTK, students act as observer, Model II, student and teacher think the problem solving in class, teacher implemented the solution and student observed, lecture did monitoring and guiding. Model III, teacher and students or only student formulating the solving of problem in the class, student applied the solution, teachers and lectures did monitoring and guiding. Lecturers, students and teachers positively response to the implementation of the CAR collaboration, but Expert judgment showed Model II as ideal model for collaboration between university and school.